Environmentally sustainable transitions of US district energy systems: Perspectives from infrastructure operators/designers through the co-evolutionary lens. (20th September 2020) - Tong, Kangkang; Ramaswami, Anu; Feiock, Richard
Abstract: Advanced district energy systems can improve local sustainability through reducing energy used for heating and cooling buildings. However, district energy systems (DESs) and their transitions are overlooked by US communities in their sustainable agendas. This research applied the multi-level perspective and co-evolutionary framework to investigate DESs' transition context and niche level practices from DES operators'/designers' perspectives. Document review approach was adopted to delineate DESs' transition context. Fourteen semi-structured interviews were conducted to investigate DES operators'/designers' visions and how they interact with factors related to ecosystems, technology, institutions, and users for near-term transitions. This research found that DESs in the US served about 10% and 12% of fully air-conditioned floor space for heating and cooling, respectively. About 93% of services provided by DESs in the US were powered by fossil fuels, and 79% of DESs distributed steam. Current federal and state policies play limited role in promoting DESs, while local policies can only encourage niche-level innovations. Results from interviews demonstrated that DES operators/designers foresaw that DESs would move toward the advanced ones. DES operators/designers were motivated by the users' demand and emerging local policy preferences to take action. Thus, DES operators/designers emphasized the importance of working closely with users and policymakers, engaging potential customers, and tapping into technical expertise during the process of transition. These results indicate that DES operators/designers took on many responsibilities with limited policy and market support. With low pressure to select DESs as a key sustainability tool at the regime level, the sustainable transition of DESs in the U.S. may only remain at the niche level. Highlights: Document review and qualitative method are adopted in this study. US DES operators delineate near-future changes. Regime context is not in favor of DESs' sustainable transitions. DESs slowly move to the advanced ones with limited local policies' and users' support. DES operators need to advocate the transition among users and local policy actors.